Impact of Front Line Demonstration on Integrated Management of Brinjal Shoot and Fruit Borer (Leucinodes orbonalis Guenee) in Nagarkurnool District, Telangana state - Shankar, Adhi; Reddy, T. Prabhakar; Reddy, M. Jagan Mohan; Jhan, Afifa; Rajashekhar, M.; Rajashekhar, B.; Ramakrishna, K.; Bhatt, P. Spandana (International Journal of Bio-resource and Stress Management, 2022)
The front line demonstrations were organised in 30 farmers fields during 2017–2020 in Nagarkurnool district. The IPM strategy included clipping and disposal of infested shoots, removal of fruits with boreholes, installation of pheromone traps @ 25 ha-1, spraying of Bacillus thurinjiensis @ 1 g l-1 and Emamectin benzoate 5% SG @ 0.4 g l-1. The mean of the parameters in 30 demonstrations during three years (pooled) revealed that shoot and fruit borer damage at a vegetative phase as shoot damage was 18.29% in demo field and 29.92% in farmers practice. Fruit damage was recorded low 23.02% in the demo field while in farmer’s practice it was 47.37%. Higher marketable fruit yield was recorded 274 q ha-1 in demo field and 17.6% yield increased over farmers practice (233 q ha-1) with benefit Cost Ratio of 2.97:1 and 2.11:1, respectively. Besides this, number of pesticide sprayings reduced significantly in the demo field (5.2 times) when compared to farmers practice (13.13 times). It is also observed that higher gross returns (Rs. 264700 ha-1) and net returns (Rs. 201806 ha-1) were recorded in the demo field than farmer’s practice (Rs. 264700 and Rs. 131496, respectively). The technology gap and extension gap enumerated from this study ranged 252-367.5q ha-1 and 28.5-63.81 q ha-1 respectively with the technology index of 54% during demonstration years. The results clearly showed that the positive impact of front-line demonstrations over farmer’s practice towards increasing the productivity and reduce the cost of cultivation of Brinjal in Nagarkurnool dist. of Telangana State.